Sosialisasi Digitalisasi Koperasi Berbasis Ekonomi Syariah di Desa Kalijaya - Ali Nur Ahmad; Sarwo Edy; Listian Indriyani Achmad; Kisanda Midisen; Nenda (DPPM Universitas Pelita Bangsa, 2021)
Digitalization has an important role in changing the world of cooperatives today. In this essay, we will discuss why digitization is so important for cooperatives and how it can provide significant benefits. First of all, digitization allows cooperatives to increase their operational efficiency. By utilizing digital technology, cooperatives can automate internal processes such as financial management, administration and inventory. This reduces the need for time-consuming and resource-intensive manual work, allowing cooperatives to allocate their time and energy for more important matters, such as improving services to cooperative members. In addition, digitalization also helps cooperatives face increasingly fierce competition in this era of globalization. With the existence of a digital platform, cooperatives can increase their visibility in the global market and reach a wider range of customers. They can use social media, websites and mobile applications to promote their products and services, establish relationships with customers and facilitate online transactions. In this way, cooperatives can expand their market share and increase revenue. In addition to better operational and marketing efficiencies, digitization has also enabled cooperatives to provide better services to their members. In this digital era, customers expect convenience and comfort in transactions. By adopting technologies such as online banking services, digital payments, or mobile applications, cooperatives can meet these expectations and provide a better experience for their members. This can create a stronger relationship between the cooperative and members, and increase their satisfaction. Finally, digitization also plays a role in driving cooperative innovation and growth. By using the latest technology, cooperatives can develop new products and services that are more relevant to today's market needs. They can track consumer trends, analyze data and use artificial intelligence to optimize their operations. By adapting to technological changes, cooperatives can remain relevant and sustainable in this digital era. Overall, digitization is very important for the cooperative world. By leveraging digital technology, cooperatives can improve operational efficiency, face global competition, provide better service to members, and drive innovation and growth. In this digital era, cooperatives need to adapt and take advantage of the opportunities offered by technology to ensure their sustainability and future success.